Synthesis and Anticancer Evaluation of Novel Benzothiazole Derivatives - Sekar, V.; Perumal, P.; Gandhimathi, S.; Jayaseelan, S.; Rajesh, V. (Asian Journal of Chemistry, 2010)
In present study novel series of benzothiazole derivatives were synthesized and their anticarcinogenic efficacy was analyzed using cancer cell lines (human small cell lung carcinoma, mouse melanoma cell line and human larynx epithelial carcinoma). The compounds were synthesized by simple and facile procedures and characterized by IR, 1H NMR and mass spectra study. The synthesized compounds were screened for anticarcinogenic activity using in vitro assays. The compounds were found to exhibit moderate anticarcinogenic activities in all cell lines. Among the synthesized six compounds, T2 showed significant activity in all cell lines.